Iot Monitoring Using ESP8266 on Solar Powered Aerator - Yosi Apriani; M. Aidil Dwiansyah; Wiwin A Oktaviani; Muhammad Hurairah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Shrimp is one of the prima donnas of Indonesia's mainstay exports from the fishery sector which needs to be improved both in terms of quality and quantity. The use of aerators as an effort to improve the quality and quantity of harvest used by pond farmers today generally still uses a manual system, where the operation of the aerator is still based on experience, not from the quality of dissolved oxygen in the pond needed by fish or shrimp in the pond. In this study, the application of an aerator to improve the quality of dissolved oxygen both in quality and quantity, is equipped with an IoT (Internet of things) method that can instruct the aerator to operate as desired using a smartphone. The components used in this tool consist of solar cell panels as renewable power plants, Aerator Pumps, and ESP8266 WiFi. In this data collection activity, in fluctuating weather conditions. Especially during rainy conditions, data retrieval is paused because test conditions do not allow it to produce a current data reading of 0 amperes. From the logger data recording, it can be seen that the highest current value that can be absorbed through solar panels is 2.40 Amperes obtained on day 3 of testing